2021
DOI: 10.4314/ahs.v21i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of adult individuals with intestinal stomas in Uganda: a cross sectional study

Abstract: Introduction: Intestinal stomas remain important life-saving surgical options in a wide range of gastrointestinal pathologies globally. Living with a stoma has potential to impair the patient’s quality of life, often with associated negative psychological effects. Objective: To evaluate the quality of life among intestinal stoma patients under Mulago National Referral Hospital (MNRH), with emphasis on psychological effects and effects on family-social interactions. Methodology: A cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
(39 reference statements)
3
18
0
3
Order By: Relevance
“…Both diagnostic and screening tools were used to assess depression among different populations in Uganda ( Table 1 ). The tools used included: (i) Depression sub-section of the Hopkins Symptom Checklist (DHSCL) ( n = 34, 26.8%) [ 35 , 55 , 61 , 63 , 65 68 , 71 , 73 , 74 , 79 82 , 84 , 92 , 100 , 108 , 110 , 111 , 113 , 125 , 135 , 136 , 138 , 140 , 141 , 144 , 147 , 151 , 155 , 166 ], (ii) Patient Health Questionnaire (PHQ) ( n = 33, 26.0%) [ 16 , 21 , 32 , 34 , 36 , 37 , 52 , 86 , 88 90 , 93 , 98 , 99 , 101 , 102 , 112 , 116 118 , 120 123 , 126 128 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both diagnostic and screening tools were used to assess depression among different populations in Uganda ( Table 1 ). The tools used included: (i) Depression sub-section of the Hopkins Symptom Checklist (DHSCL) ( n = 34, 26.8%) [ 35 , 55 , 61 , 63 , 65 68 , 71 , 73 , 74 , 79 82 , 84 , 92 , 100 , 108 , 110 , 111 , 113 , 125 , 135 , 136 , 138 , 140 , 141 , 144 , 147 , 151 , 155 , 166 ], (ii) Patient Health Questionnaire (PHQ) ( n = 33, 26.0%) [ 16 , 21 , 32 , 34 , 36 , 37 , 52 , 86 , 88 90 , 93 , 98 , 99 , 101 , 102 , 112 , 116 118 , 120 123 , 126 128 , …”
Section: Resultsmentioning
confidence: 99%
“…Depression among special patient groups in Uganda. The prevalence of depression ranged from 0.4% among outpatients in northern Uganda [109] and 88% among patients with stomas [32]. The prevalence among those who (i) were elderly was 18% [57], (ii) had tuberculosis was 23.7% [152], (iii) had post-tuberculosis lung diseases was 24% [122], (iv) had cancer was 26% [17], (v) with post-stroke was 31.5% [131], (vi) were physically ill was 33.7% [124], (vii) had diabetes mellitus was 34.8% [115], (viii) had sickle cell disease was 68.2% [54], and (ix) had rheumatoid arthritis was 70.8% [33].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…These included studies conducted between 2011 and 2021, where participants ranged from 29 to 1,903. Two studies involved participants of any of two genders [i.e., female ( 65 ) and male ( 53 )], whereas the lowest number of female participants was 11 ( 66 ) and the highest was 1,492 ( 39 ), and the percentage of female participants ranged from 21% ( 66 ) to 82% ( 48 ). Most of the studies reported participants' mean age ( n = 37), ranging between 31 and 45 years.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that the psychosocial needs and anxiety arising from the stoma formation were also significant in predicting patients' psychosocial behavioral reactions post-stoma (15). Despite the presence of multiple studies examining the prevalence of anxiety and depression among these patients, there has not yet been a meta-analysis to establish the prevalence of depressive symptoms in patients with stomas, or to ascertain whether stoma placement is associated with a higher risk of depression in patients (16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%